957 THE USE OF IPADS AS PART OF PERSON CENTERED CARE IN A TEACHING HOSPITAL IN SINGAPORE. (14th June 2022) - Oo, T; Aung, Z; Barrera, V; Arroyo, S; Lim, S
Abstract: The elderly patients are currently the main occupants of acute hospital beds and this trend will likely increase as the world ages. The elderly patients with cognitive issues frequently have behavioural symptoms which may be challenging for the care staff to manage, especially the staff who have not been formally trained in Gerontology. The use of restraints for this group of vulnerable patients should be discouraged as restraints can cause harmful effects. The use of iPads as a non pharmacological strategy for managing the behavioural symptoms among the elderly in-patients with cognitive issues was effective in reducing agitation, with an improvement in mood and sundown symptoms. The patients were actively and meaningfully engaged with their iPads during therapy. The nursing staff too, benefited from iPads as a novel therapy for their elderly in-patients with cognitive issues in providing cognitive and social stimulations, which they had no time to provide for. While the patients showed improvement in their behavioural symptoms, the nurses' stress levels reduced with improved self-reported job satisfaction.